Functional Outcomes of Peroneal Reconstruction with Peroneal Tendon Transfer. Issue 3 (11th September 2017) - Jaffe, David; Vier, David; Kane, Justin; Brodsky, James
Category: Hindfoot Introduction/Purpose: Tears of the peroneal tendons are a frequent cause of pain and disability. Surgical intervention is frequently warranted for symptoms that persist despite conservative management. Surgical treatment can include repair, local tendon transfers (i.e. peroneus longus to brevis transfer), or allograft reconstruction. While allograft reconstruction has been advocated for reconstruction of even a single peroneal tear, the indications are not widely agreed upon. The hypothesis of this study was that reconstruction with excision of the diseased tendon and transfer to the adjacent peroneal tendon produces significant improvements in both pain and function. Methods: Patients that underwent surgical intervention for peroneal tendon pathology at a single institution by a fellowship- trained foot and ankle orthopaedic surgeon were prospectively followed. Operative reports were reviewed to identify patients that underwent peroneal reconstruction with excision of the diseased tendon and local tendon transfer for chronic, severe peroneal tearing. Preoperative AOFAS and Visual Analog Scores (VAS) were obtained as a baseline and then repeated at one year following surgery. Statistical analysis was performed to compare preoperative and postoperative pain and function. Results: 14 patients were identified that underwent peroneal reconstruction without allograft tendon using reconstruction with excision of the diseased tendon and transfer to the adjacent peroneal tendon. Average age was 41.2 years (range 23-61 years) and average follow-up was 26.7 months (range 12-67 months). At one year, patients' AOFAS scores improved from 51.9 +/- 12.2 to 90.7 +/- 3.4 (p<0.0001). VAS scores decreased from 6.5 +/- 1.2 to 1.6 +/- 0.9 (p<0.0001). There was 100% survivorship of the reconstruction procedure at one year. One patient underwent an allograft reconstruction for recurrent tearing five years after initial surgery and no other patients underwent a revision procedure. Demographic data and functional scores before and after surgery are displayed in Table 1. Conclusion: Peroneal reconstruction performed via excision of the torn tendon and local transfer to the adjacent tendon results in clinically significant improvement in pain and function without the need for allograft tissue. Patients may be counselled that peroneal transfer for chronic, severe tears leads to significant improvement and excellent clinical outcomes. This study shows excellent results can be obtained with local tendon transfer and the authors advocate this procedure to avoid the cost and risk of allograft transplant.